Formation of adaptive dynamic scenarios in computer educational systems - Артамонов, Євген Борисович; Панфьоров, Олександр Володимирович (Technology audit and production reserves, 2016)
Considered dynamic scenarios in adaptive educational systems have the following disadvantages: Insufficient analysis of learning estimation classifiers. Little attention is given to estimation of focus attention on the material. To address these issues in the study materials we use the works of other scientists that is devoted to adaptive methods of presentation and testing in educational systems. Process formalization of building a knowledge base is done using semantic networks and an estimation of the minimum and maximum limit of the number of rules is obtained. The minimum number of test questions on the topic to form linear plots is within 3-5 (depending on the topic complexity), the maximum number of questions – 11. Estimation algorithms within adaptive educational courses for learning control are implemented. Requirements to tests are formed as a part of the estimation algorithms, which include: Independent of the tasks. Simplicity and compactness of question formulation. Exclusion of ambiguous question understanding. The complex model of the educational process is developed using information technologies. This model includes presentation of technological, targeted, meaningful and effective system components and their relationships (substantiation of learning objectives, content modules of curriculum, conditions for achieving goals, learning activities of students and teachers, learning results). This model allows to use approaches for building of dynamic scenarios, which include the principles of non-linearity of the plot, a variety of solutions, loose problem solutions, variety of ways to pass educational courses.